Reform of Indonesian Capital Market Governance in Response to MSCI's Evaluation of Transparency and Trading Manipulation: Reform of Indonesian Capital Market Governance in Response to MSCI's Evaluation of Transparency and Trading Manipulation - Arya Elang Anom; Zulfikri Toguan; Azbi Arief Habibi (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2026)
This study examines the reform of Indonesian capital market governance in the context of market accessibility assessment conducted by MSCI (Morgan Stanley Capital International). Using a normative juridical method and a qualitative-descriptive approach, the research analyzes three main issues: the regulation of stock trading transparency, forms of market manipulation that have become concerns for MSCI, and the ideal framework for regulatory reform. The findings reveal that the Indonesian capital market legal framework, which is based on Law Number 8 of 1995 concerning Capital Markets and Law Number 4 of 2023 concerning the Development and Strengthening of the Financial Sector (P2SK Law), has established a foundation for transparency through the principles of full disclosure and material information disclosure. However, the existence of 32 alleged market manipulation cases handled by the Financial Services Authority (OJK) up to early 2026 indicates persistent regulatory gaps, particularly in addressing digital trading practices such as spoofing and front running. MSCI’s evaluation also highlights limitations in ESG and non-financial data disclosure among Indonesian listed companies. This study recommends the reformulation of the legal status of tippees, the adoption of the misappropriation theory, the integration of artificial intelligence-based RegTech and SupTech systems, and the strengthening of the enforceability of capital market arbitration awards. These reforms are expected to enhance market integrity, transparency, and investor confidence, thereby improving Indonesia’s competitiveness in the global capital market.